THE EFFECTS OF COMMUNITY ACQUIS (ACQUIS COMMUNAUTAIRE) ON PROVISIONS OF THE NEW TURKISH COMMERCIAL LAW CONCERNING PUBLIC LIMITED LIABILITY COMPANIES - Boyacioglu, Cumhur; Ercan, Ibrahim (European Scientific Journal, ESJ, 2013)
﻿One of the most important recent changes in Turkish economical life is the new Commercial Law. The new Law serves as the most important medium for the approximation and harmonization of the Turkish company law to the company laws of the Member States. It allows the right of establishment and free movement of capital. The protection granted to the minority shareholders and creditors of the company has been strengthened. Corporate governance has been a key feature applicable to all enterprises. Single shareholder limited liability companies are allowed. As a result, the new regulation seems to correspond with the requirements of the community acquis and has been profoundly affected by the various directives regarding company law.